Intercontinental hearing assessment - a study in tele-audiology. - Swanepoel de W; Koekemoer D; Clark J (Journal of Telemedicine & Telecare, 2010)
We evaluated the validity of remote pure tone audiometric testing conducted from North America on subjects in South Africa. Desktop-sharing computer software was used to control an audiometer in Pretoria from Dallas, and PC-based videoconferencing was employed for clinician and subject communication. Thirty adult subjects were assessed, and the pure tone audiometric thresholds (125-8000 Hz) obtained through conventional face-to-face and remote testing were compared. Face-to-face and remote audiometry thresholds differed by 10 dB in only 4% of cases overall. The limits of agreement between the two techniques were -8 and 7 dB with a 90% confidence interval of -5 to 5 dB. The average reaction times to stimulus presentations were similar, within -108 and 121 ms. The average test duration was 21% longer for remote testing (10.4 vs. 8.2 min). There were no clinically significant differences between the results obtained by remote intercontinental audiometric testing and conventional face-to-face audiometry. It may therefore be possible to expand the reach of audiological services into remote underserved regions of the world.